Improved Robust LQR Digital Control Method for High Bandwidth Inverters With Time Delay and Uncertain Parameters - Jichao Ning; Hongqi Ben; Xuesong Wang; Tao Meng (IEEE Open Journal of Power Electronics, 2023)
A feedforward combined with state feedback linear quadratic regulator (LQR) is proposed to reduce the output waveform distortion and load regulation of high-bandwidth inverters. However, when digital control is adopted, the additional delays introduced by each part can lead to unmodeled model errors, which not only seriously affects the stability of the system, but also complicates the design of the controller. Therefore, a method of converting the design of a digital control system into time domain pole position selection is proposed to simplify the analysis and design of the controller, and can easily convert the time domain control method into the corresponding digital control. Furthermore, to ensure system stability in the presence of parametric uncertainties in the filter components and input bus voltage, robustness to parametric uncertainties is incorporated into the proposed digital control method. The feasibility, effectiveness and superiority of this method were verified through simulation comparison and experiments.